Garlic - a powerful plant - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Canisius Mpala, a garlic farmer from Zimbabwe explains the advantages of this crop, for which the market in Africa is growing.